An Accessory Muscle of Pectoral Region: A Case Report - B.M. Bannur; Nagaraj Mallashetty; Preetish Endigeri (Journal of Clinical and Diagnostic Research, 2013)
Among the variations of pectoral muscles, this case appears to be unique in the literature. This was a case of an accessory pectoral muscle which was located between pectoralis major and pectoralis minor muscles, which was discovered during a routine anatomy dissection. The accessory muscle originated from 6th and 7th ribs at costo-chondral junction, which travelled supero-laterally and inserted by fusing with fibres of pectoralis minor . This unusual muscle holds importance for surgeons while they perform dissectomies, in avoiding complications.